GREEN PERCEIVED RISK, GREEN VIRAL COMMUNICATION, GREEN PERCEIVED VALUE AGAINST GREEN PURCHASE INTENTION THROUGH GREEN SATISFACTION - Juliana, Juliana; Djakasaputra, Arifin; Pramono, Rudy (AGUSPATI Research Institute, 2020)
The purpose of this study is to analyze the significant effect of green perceived risk on green purchase intention, to analyze the significant effect of green viral communication on green purchase intention, to analyze the significant effect of green perceived value on green purchase intention, to analyze the significant effect of green satisfaction on green purchase intention to analyze the significant effect of green perceived risk on green satisfaction, to analyze the significant effect of green perceived value on green satisfaction, to analyze the significant effect of green viral communication on green satisfaction. The population in this study consumers of green product users in Medan The sample in this study consisted of 100 respondents. The data collection method uses a questionnaire with random sampling techniques and data analysis uses EVIEWS 10. The data collection method also uses a Likert scale questionnaire data one to six. The results of the analysis using eviews 10 resulted that there was a significant effect of green perceived risk on green satisfaction, there was no significant effect of green viral communication on green satisfaction, there was a significant effect of green perceived value on green satisfaction, there is a significant effect of green perceived risk on green purchase intention, there is no significant effect of green perceived value on green purchase intention, there is a significant effect of green satisfaction on green purchase intention, there the significant effect of green viral communication on green purchase intention.